Predicted skeletal muscle index as a scalable marker for sarcopenia risk and mortality in older Chinese adults - Liu, Ya; Qi, Yingsong; Wang, Huanhuan; Zhao, Xiaojing; Zhang, Min; Ma, Liangyan; Huang, Lan; Dong, Qiaorong (Frontiers in Medicine, 2025)
Background and aimsSarcopenia, characterized by age-related loss of muscle mass and function, increases adverse outcomes in older adults. The predicted skeletal muscle mass index (pSMI), derived from serum creatinine and cystatin C, may serve as a practical biomarker. This study evaluated pSMI’s ability to predict sarcopenia and mortality in older Chinese adults.MethodsWe analyzed 5,982 adults aged ≥60 years from the 2015 China Health and Retirement Longitudinal Study (CHARLS). pSMI was calculated using a sex-specific formula and categorized into quartiles. Sarcopenia was defined per Asian Working Group for Sarcopenia 2019 criteria. All-cause mortality was tracked over 5 years (2015–2020). Logistic regression assessed pSMI’s association with sarcopenia, and Cox models evaluated mortality risk, adjusting for demographics, behaviors, comorbidities, and inflammatory markers.ResultsSarcopenia prevalence decreased from 55 to 67% in the lowest pSMI quartile (Q1) to 0.4% in the highest (Q4). Higher pSMI reduced sarcopenia odds by 97–99% in Q3–Q4 vs. Q1 (p < 0.001). Five-year mortality fell from 23.4% (men) and 13.6% (women) in Q1 to 9.0 and 3.9% in Q4. Adjusted hazard ratios for mortality in Q4 vs. Q1 were 0.47 (95% CI: 0.32–0.70, men) and 0.38 (95% CI: 0.22–0.65, women).ConclusionpSMI strongly predicts sarcopenia and mortality in older Chinese adults. To our knowledge, this represents the first large-scale validation of pSMI’s prognostic value for mortality risk independent of baseline sarcopenia in a nationally representative older Chinese cohort. As a blood-based biomarker, pSMI may serve as a practical screening tool and prognostic marker, facilitating timely interventions such as nutritional support and resistance exercise.